Análise do processo comunicacional por meio de tecnologias móveis e sem fio na gestão de desastres naturais - Silva, Sônia Regina da (Universidade do Vale do Rio dos Sinos, 2018)
The combination of severe weather events and natural disasters has raised concerns in all societies. Globally, international agencies promote and coordinate disaster risk reduction and prevention initiatives and call on nations for such a commitment. In Brazil, a breakthrough occurred with the institution of the National Protection and Civil Defense Policy through Law 12,608/2012, which, among other aspects, reorients disaster risk management, which comprises three distinct and interrelated actions: prevention, mitigation and preparation. These occur in a multisectoral manner at the federal, state and municipal levels and require broad community participation. Mobile and Wireless Information Technologies are emerging in this context, whose development over the last two decades has highlighted them as important resources for assistance in unexpected and disruptive scenarios and play an increasingly positive role as tools for communicating disaster risk. This study aims to analyze how the communication process occurs in flood risk management, through the use of Mobile and Wireless Technologies, between civil defense institutions and the population established in flood areas. It also seeks to identify the perception of the actors about the quality of the information received from mobile technologies and the advantages and disadvantages of their use in risk communication. As a research strategy, a single case study was carried out in a city in the interior of the State of Santa Catarina, which almost annually faces the problem of floods. The study concludes that mobile technologies and mobile social media are effective and efficient tools in risk communication, since they increase the possibilities of access and dissemination of alerts; stimulate, facilitate and boost the interaction of the population with the civil protection and defense organs and contribute positively to the mobilization in the face of the disaster, since they speed up the transmission of information, favoring the planning for the evacuation of areas at risk. Already, the false news transmitted by mobile media and the risk of lack of connection and energy characterize some of the disadvantages of using these technologies.
Keywords: Comunicação de risco; Gestão do risco de desastres; Mídias sociais; Tecnologias móveis; Risk communication; Disaster risk management; Social media; Mobile technologies; ACCNPQ::Ciências Sociais Aplicadas::Administração